Evaluation of the efficacy of the in vitro micronucleus method using a commercial kit and comparison with the microscopy method - Silveira, Karine Renata Dias; Brunel, Hilana dos Santos; Andrade, Rosângela Vieira de (Seven Editora, 2023)
In vitro micronucleus testing is an important tool in the investigation of the genotoxic potential of products. Performing the test by the optical microscopy method requires training and attention from the technician reading the slides and can be an extremely slow process. The technique of micronucleus analysis by flow cytometry emerges as a highly complex assay that makes it possible to increase the number of analyses and reduce the time spent on experiments. Some commercial kits are sold to perform this test, however, in some cases, they can be very costly for the laboratory. This work demonstrated that the technique of micronuclei in vitro by microscopy and cytometry are equivalent and that it is also possible to optimize the use of commercial reagents to reduce costs. DOI:https://doi.org/10.56238/sevened2023.004-059